Does the DM Dominate the Euro Market? An Empirical Investigation - Kirchgassner, Gebhard; Wolters, Jurgen (The Review of Economics and Statistics, 1993)
Starting point is the 'German Dominance Hypothesis, ' according to which Germany has a dominant position within the EMS. This makes it impossible for other member countries to pursue their own monetary policies. Using monthly data of three-month Euro market rates from 1980 to 1988, for the U.S., Germany, the U.K., the Netherlands, France and Italy, we test this hypothesis in a multivariate cointegration framework. We find that Germany has a strong position in Europe, which is not restricted to the EMS. Concerning long-run development, one might speak of a dominant position. However, there are short-run relations between European countries which are not linked to relations with Germany. Copyright 1993 by MIT Press.